Meningitis Tuberculous with Miliary Tuberculosis and Thoracic Vertebrae Level 11-12 Tumor showing Neurofibroma Patterns: A Case Report - Wijayanto, Andi; Muktiati, Nunuk Sri; Bal’afif, Farhad; Rianawati, Sri Budhi (Malang Respiratory Journal, 2019)
Background: Tuberculosis is an infectious disease that develop from systemic infection caused by bacterium Mycobacterium tuberculosis complex. Generally, M.tuberculosis spread from one person to another through nuclear droplet air transmission. Although TB has a lower transmission rate compared to another infectious disease, TB still become a global health problem. It is estimated that approximately one third of the world’s population is infected by tuberculosis. Every year it is estimated that there are nine million new cases and close to two million death cases caused by tuberculosis.Case: A 24-year-old female was admitted to the hospital complaining of could not move both of her legs and could not urinate. One month before admission, she was diagnosed with meningitis TB; miliary TB; and meningioma at thoracic vertebrae T11-12 based on physical examination, laboratory examination, Chest X-Ray, Head CT Scan without contrast, and thoracolumbal MRI. When admitted to the hospital, the patient already treated with Fixed Dose Combination of antituberculosis Drugs first category for one and a half month from Turen Primary Healthcare. Then the patient underwent bronchoscopy examination. The result of the anatomical pathology examination showed class two. Then the patient underwent a laminectomy surgery and tumor excision at thoracic vertebrae T11-12. The result of postoperative Anatomical Pathology examination showed a neurofibroma pattern. After surgery, the Physical Medicine and Rehabilitation Department placed thoracic lumbosacral orthoses (TLSO) to the patient. Postoperative evaluation up to three months showed that the patient’s general condition was quite good but still cannot move both of her legs and cannot urinate.